Revitalisasi Kader Sebagai Motivator Kesehatan Pra-Kehamilan Melalui Inovasi Media Komunikasi - Nabila Khusna Amalia; Ayik Mirayanti Mandagi; Ira Nurmala; Rachmat Hargono; Desak Made Sintha Kurnia Dewi; Jayanti Dian Eka Sari; Syifa’ul Lailiyah; Diansanto Prayoga; Susy Katikana Sebayang; Septa Indra Puspikawati; Mohammad Zainal Fatah (Universitas Negeri Malang, 2021)
Maternal Mortality Rate and Infant Mortality Rate is still far from the target of SDGs 2030 is an indicator depicting low society prosperity in Indonesia. One of the factors were due to Women of Fertile Age at risk of Chronic Energy Deficiency at age 15 until 19 years. This situation is exacerbated by the high age of marriage less than 20 years which certainly interfere with reproductive health. Nutrition motivationer program in Banyuwangi isn’t optimal yet because it does not cover health aspect pre pregnancy and cadre isn’t functioning as health motivationer. Therefore, it is necessary to empower the cadres to optimize the health service. The aimed to increase cadre knowledge about pregnancy and reproductive health as well as to improve cadre communication skill as health motivationer. The conducted in Segobang Village, District of Licin, Banyuwangi on September 2016. The target was Segobang Village cadres who are active in Posyandu. Then result was more than 67 percent knowledge of cadres were good and 94 percent of cadre knowledge increases. Communication skills were demonstrated by the evaluation of Women of Fertile Age that comes during simulation, almost all cadres can deliver well and clearly so understood by the woman. It was be concluded that almost all cadre increased him knowledge according to pre-test and post-test questionnaires. Communication skills of the cadres showed good results.